Interprofessional collaborative practice is an effort to increase behavior prevention of stunting in families with the first 1000 days of life - Dwiana Estiwidani; Munica Rita Hernayanti (Jurnal Kesehatan Ibu dan Anak, 2021)
Indonesia is one of 17 countries that experience stunting problems. Compared to several neighboring countries, Indonesia ranks highest. Various attempts have been made but have not shown a significant decline. Other alternative efforts need to be made to prevent stunting in an integrated manner with Interprofessional Collaborative Practice (IPCP). This study aimed to know the effect of IPCP on Increasing Stunting Prevention Behavior in Families with the first 1000 days of life in the Gedangsari II Health Center in Gunungkidul Regency. With a long-term goal to prevent stunting problems in Gunungkidul Regency. This study was experimental research with a pretest-posttest with a control group design. Location in Wonosari District. The number of samples was 50 families, both in the intervention group with IPCP and in the control with a standard program from the Puskesmas. Data collection instruments are in the form of behavior observation sheets. Bivariable analysis using paired sample t-test and independent sample t-test, Wilcoxon and Mann-Whitney. The mean of prevention behavior of the stunting pre-test intervention group was 70,224 and the control 71,564, the average prevention behavior of the stunting post-test intervention group was 75,312 and the control 73,580, the increase in mean of prevention behavior of stunting pre-post-intervention group 5,048 and control 2,068. There was a difference in the increase in the mean of stunting prevention behavior at pre-post between the two groups (p-value <0.05), IPCP could increase stunting prevention behavior by 27 times controlled by the variable number of family members. Interprofessional Collaborative Practice (IPCP) affected increasing stunting prevention behavior in families with the first 1000 days of life in the Gedangsari II Health Center in Gunungkidul Regency.